Andean linguistics in the context of the peruvian-bolivian altiplano: a personal testimony - Cerrón-Palomino, Rodolfo (2017)
The article focuses on the progress and development of the studies in Andean linguistics with particular reference to Quechua, Aymara, Uro and Puquina. These languages converged at certain period in history as an idiomatic crossroad on the immense altiplano (now shared by Peru and Bolivia), cradle of the Andean civilization. Some of these languages still exist, others have left a silent legacy that enriches the culture of the survivors imprinting an indelible stamp on the plentiful toponymy that only awaits the specialized linguist capable to read the historical ancestral messages coded in place names.